2010
DOI: 10.1158/0008-5472.can-09-3982
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-Associated Fibroblasts Enhance the Gland-Forming Capability of Prostate Cancer Stem Cells

Abstract: Signals originating from cancer-associated fibroblasts (CAF) may positively regulate proliferation and tumorigenicity in prostate cancer. In this study, we investigated whether CAFs may regulate the biology of prostate cancer stem cells (CSC) by using a conditional Pten deletion mouse model of prostate adenocarcinoma to isolate both CAF cultures and CSC-enriched cell fractions from the tumors. CSCs that were isolated possessed self-renewal, spheroid-forming, and multipotential differentiation activities in tis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
104
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(107 citation statements)
references
References 40 publications
3
104
0
Order By: Relevance
“…Analysis of tumour-forming ability and spontaneous lung metastasis formation after contact with CAFs revealed that the activated stroma contributes to generate a population of prostate cancer stem cells with defined ability to form primary tumours and distant metastases [23]. In keeping with this, in a conditional Pten deletion mouse model of prostate adenocarcinoma, CAFs confirm their key role in the regulation of stemness properties as they enhance spheroid formation and prostate glandular structures with lesions, high proliferative index and tumour-like histopathology [90].…”
Section: Regulation Of Motility and Stemnessmentioning
confidence: 57%
“…Analysis of tumour-forming ability and spontaneous lung metastasis formation after contact with CAFs revealed that the activated stroma contributes to generate a population of prostate cancer stem cells with defined ability to form primary tumours and distant metastases [23]. In keeping with this, in a conditional Pten deletion mouse model of prostate adenocarcinoma, CAFs confirm their key role in the regulation of stemness properties as they enhance spheroid formation and prostate glandular structures with lesions, high proliferative index and tumour-like histopathology [90].…”
Section: Regulation Of Motility and Stemnessmentioning
confidence: 57%
“…As for the involvement of the CAF-mediated culturing condition of CSCs, established CAFs enriched self-renewal, spheroid-forming and multipotential differentiation in Lin– SCA-1+ CD49f+ prostate CSCs [48]. However, we show that BM-MSC mediated the restoration of CD133+ MKN-7 cells, resulting in higher tumorigenicity and pluripotency.…”
Section: Discussionmentioning
confidence: 74%
“…4B). Nor does it disagree with the fact that CD133 þ isolates cancer repopulating cells within the tumor itself [12,27,31]. It does, however, raise the possibility that normal stem cells and cells of origin of cancer, within the basal compartment, are not necessarily the same cells, and the latter may involve rapidly proliferating or transient-amplifying cells within the basal cell fraction, as was originally postulated by Vander Griend et al [27].…”
Section: Discussionmentioning
confidence: 91%